Grammatical Frontiers in Translation: Navigating Morphological and Syntactic Terrain for Fidelity and Coherence - Tishabayevna, Nurova Gulchehra; qizi, Kuchkarova Noila Abduvahob (Journal of Innovation in Education and Social Research, 2024)
Translation plays an important role in social life. Since translation is not an easy work, the translators should carry out a good amount of knowledge in linguistics, cultural aspect, and other skill related to human life. Occasionally, a faulty in translation causes a violation in the result and is inacceptable in the target text. The aim of this research is to identify the grammatical problems.